Effectiveness of Nursing Management Education Program upon the Nurse Managers' Knowledge about Planning in Baghdad City Hospitals - Yasir, Amean; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2010)
Objective: To determine the effectiveness of the Nursing Management Education Program upon the NurseManagers' Knowledge about planning in Nursing Management at Baghdad City Hospitals.Methodology: A Quasi-experimental study in which a purposive "non-probability" sample of (50) NurseManagers was selected from Baghdad City Hospitals. These Managers were divided into two equal groups of(25) Nurse Managers for each (study and control ones). A questionnaire was developed as a tool for datacollection. A pilot study was carried out to test the reliability of the questionnaire for the period from April 2nd toJune 20th 2007. The pre-post test approach was applied to the study and control groups as mean for the quasiexperimentaldesign when the education program was implemented in the period from October 1st 2007 toFebruary 1st 2008. Data were analyzed through the application of the descriptive data analysis approach(frequency, percentage, mean) and inferential data analysis approach (T-test).Results: The study results revealed that the study group participants made use of the implementation of nursingmanagement program and a change had occurred to their knowledge about planning in nursing management. Thestudy concludes that the nursing management education program can be considered an effective mean for theimprovement of the nurse managers' knowledge about planning in nursing management.Recommendations: The study recommends that the nursing management education program can be presented toall nurse managers with respect to planning in nursing management.